Development of scientific-based student worksheets to improve science process skills through problem-based learning - Siti Nurjanah; Muhammad Radian Nur Alamsyah; Sekar Jati Pamungkas (JPBIO (Jurnal Pendidikan Biologi), 2022)
LKS is a product that can help achieve the desired learning objectives. This study aims to determine the feasibility and effectiveness of LKS with a scientific approach to the respiratory system material to improve students' science process skills in PBL learning in high school based on the results of expert validation, science process skills (KPS) tests and observations. The research method used in this research is (R&D) and experiment. The results of the feasibility test analysis based on the results of the validation of media, material and pedagogic aspects obtained a score was 83.5%. LKS effectiveness test results of the KPS difference test between the experimental class and the control class, the sig value was obtained. (2-tailed) 0.002 and the comparison of the test results for the increase (N-gain) of the experimental class KPS was 0.40 and the control class of 0.27 and based on these results from the comparison of the KPS observations the control class gets the value of 74% while the experimental class got a value was 96%, so it can be concluded that the LKS has a scientific approach very feasible and effective to use to improve students' science process skills in PBL learning.